2020
DOI: 10.1186/s12964-019-0507-3
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of immunogenic cell death in radiation-resistant breast cancer stem cells by repurposing anti-alcoholism drug disulfiram

Abstract: Background: The current successful clinical use of agents promoting robust anti-tumor immunity in cancer patients warrants noting that radiation therapy (RT) induces immunogenic cell death (ICD) of tumor cells, which can generate anti-tumor immune responses. However, breast cancer stem cells (BCSCs) are resistant to RT and RT alone usually failed to mount an anti-tumor immune response. Methods: High aldehyde dehydrogenase activity (ALDH) bright and CD44 + /CD24 − /ESA + cancer cells, previously shown to have B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 47 publications
(64 reference statements)
2
65
0
Order By: Relevance
“…DES exposure appeared in an adjusted RR of 1.42, and gestational diabetes and soy formula had a similar RR of 1.28 and 1.25, sequentially. Although there is an inconsistency in this study: when dividing women who reported to have 'definitely' or 'probably' been exposed to DES, women exposed showed no increased risk, while those who classified as being exposed had a RR of 2.07, this study also described that experiencing menarche under the age of 10 or 11 resulted in RR of 1.54 and 1.32, respectively, and being poor had a RR of 1.24 55,82 . Another study from 85 UF cases reported an association between prenatal DES and UF risk 83 .…”
Section: (I) Prenatal Des Exposure (Ii)gestational Diabetes (Iii)pregnancy Diabetes (Mothers Who Had Diabetes Before Pregnancy) (Iv) Soy mentioning
confidence: 64%
“…DES exposure appeared in an adjusted RR of 1.42, and gestational diabetes and soy formula had a similar RR of 1.28 and 1.25, sequentially. Although there is an inconsistency in this study: when dividing women who reported to have 'definitely' or 'probably' been exposed to DES, women exposed showed no increased risk, while those who classified as being exposed had a RR of 2.07, this study also described that experiencing menarche under the age of 10 or 11 resulted in RR of 1.54 and 1.32, respectively, and being poor had a RR of 1.24 55,82 . Another study from 85 UF cases reported an association between prenatal DES and UF risk 83 .…”
Section: (I) Prenatal Des Exposure (Ii)gestational Diabetes (Iii)pregnancy Diabetes (Mothers Who Had Diabetes Before Pregnancy) (Iv) Soy mentioning
confidence: 64%
“…In radiation-resistant breast cancer cell lines, the efficacy of radiotherapy was enhanced by DSF in a Cu-dependent manner; moreover, radiotherapy alone only triggered a low level of immunogenic cell death, DSF/Cu complex was able to increase radiotherapy-induced immunogenic cell death; further investigation revealed reactive oxygen species (ROS) generation and IRE1α/XBP1 signal pathway were partially responsible for improving radiotherapy-induced immunogenic cell death. 23 These findings suggested DSF as a novel radiosensitizer in the existence of Cu for breast cancer.…”
Section: Dsf Binds To Metal Ionsmentioning
confidence: 92%
“…G44-26; Miltenyi Biotec Inc.). The ALDH þ CD44 þ PCSCs were detected by flow cytometry using a BD Accuri C6 flow cytometer (BD Biosciences) and sorted using a FACS Aria II Cell Sorter Flow Cytometer (BD Biosciences) (32).…”
Section: Fir or Single-dose Irradiationmentioning
confidence: 99%
“…FIR-treated cells were collected, washed, resuspended at a cell density of 10 6 cells/500 mL of 1X binding buffer, and stained with 5 mL of Annexin V-FITC and 5 mL of 7AAD at RT for 15 minutes in the dark. A minimum of 10,000 cells within the properly gated region was analyzed for apoptosis by flow cytometry (32).…”
Section: Apoptosis Assaymentioning
confidence: 99%